Analysis of the structural response and strengthening performance of prefabricated substation walls under flood loads - Yao, Han; Zhang, Liang; Wang, Qing; Han, Huina; Han, Fengkai; Tian, Li (Frontiers in Materials, 2023)
The reliability of prefabricated perimeter walls in substations is crucial to ensuring the safe and stable operation of internal facilities under flood conditions. To investigate the load-bearing performance of prefabricated perimeter walls under flood loads, this study establishes a refined numerical model for prefabricated perimeter walls based on actual engineering data. It conducts an analysis of key flood parameters to clarify their influence on the structural behavior of the walls. Additionally, the force transmission mechanism of the walls is investigated, and "W-shaped" reinforcement measures are proposed to address the stress characteristics of the prefabricated perimeter walls. The research findings indicate that both flood depth and flow velocity significantly influence the performance of the walls. Flood erosion has a minor impact on wall performance. However, when flood depth exceeds 1.0 m or flow velocity surpasses 3 m/s, the safety of the prefabricated perimeter walls notably decreases. The force transmission mechanism of the walls is well-defined, with larger displacements observed at higher water levels. Critical areas such as the connections between wall panels and columns, as well as wall panels and foundations, experience higher stress levels. The "W-shaped" wall reinforcement device effectively reduces wall displacement and stress.